Neuroprotective and Antiapoptotic Potential of Trigonelline in a Striatal 6-Hydroxydopamine Rat Model of Parkinson’s Disease - Mirzaie, M.; Khalili, M.; Kiasalari, Z.; Roghani, M. (Нейрофизиология, 2016)
Considering neuroprotective and antioxidant effects of trigonelline, our study was undertaken to evaluate its protective effect in a 6-hydroxydopamine-induced model of Parkinson’s disease (PD) in rats. Unilateral intrastriatal 6-OHDA-lesioned rats were pretreated with trigonelline at doses of 50 and 100 mg/kg. Significant rotational behavior, a significant reduction in the number of Nissl-stained neurons on the left side of substantia nigra pars compacta (SNC), increased apoptosis, enhanced levels of malondialdehyde (MDA) and nitrite, and a lower level of glutathione (GSH) were observed in 6-OHDA-lesioned rats. Trigonelline at a dose of 100 mg/kg significantly reduced rotations, prevented reduction of SNC neurons, prevented apoptosis, and restored the MDA level. These results suggest that pre-lesion trigonelline treatment exerts dose-dependent neuroprotective and antiapoptotic effects under conditions of 6-OHDA toxicity and may be, henceforth, advantageous for the management of early PD.